Depicting Life Through Conceptual Metaphor: an Art-Linguistic Analysis of Students’ Works in an Aesthetics Course - Kristining Seva; Ignatius Bambang Sugiharto; Asnita Sirait; Anniek Orye (JOLLT Journal of Languages and Language Teaching, 2026)
Metaphor is recognized in cognitive linguistics as a mechanism through which individuals conceptualize abstract experiences in concrete terms. While extensive research has examined metaphor in verbal discourse, comparatively less attention has been given to how conceptual metaphors work in students’ visual artworks, particularly within an aesthetics course, which is a mandatory university subject for all regular students. Investigating conceptual metaphors of ‘life’ in student artworks is valuable because it reveals how cognitive processes, disciplinary backgrounds, and multimodal resources interact in meaning-making practices. This study probes how students use visual metaphors in the aesthetics subject. Data collected from artworks, titles, essays, interviews, and discussions were analyzed; the analysis was conducted in two stages: CMT (Conceptual Metaphor Theory) was used to identify source–target mappings underlying students’ metaphors (e.g., Life is a Ladder, Life is a Reflection); MDA (Multimodal Discourse Analysis)was applied to examine how visual elements such as composition, colour, material choice, and spatial arrangement reinforced and expanded metaphorical meanings. The findings reveal a clear disciplinary pattern: students from scientific backgrounds tend to construct structured, linear metaphors, whereas students from social sciences and humanities produce more layered, abstract, and narrative-driven metaphors. This indicates the multiple cognitive structures of metaphor as an art form and their societal settings. These findings contribute to art education by demonstrating how metaphor-based pedagogy fosters reflective thinking, interdisciplinary awareness, and multimodal literacy. Moreover, the study provides empirical evidence that meaning-making of ‘life’ in art classrooms emerges through the interaction of cognitive mapping and semiotic resources.